(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
In this study, we explore teachers’ viewpoints on the concept of collegial supervision and supporting elements that are believed to advocate the collegial practice in Malaysian public secondary schools. The study equally examines the benefits of practicing collegial supervision within the sampled secondary schools. A purposive sampling technique was engaged to select and interview 15 novice and experienced public secondary teachers for data collection. The findings revealed that teachers viewed the collegial supervision (CS) platform as a means to improve teaching practices. Teachers, however, argued that the CS standards framework and implementation need to be aligned with the national education philosophy and sociocultural environment of Malaysia. Interestingly, the findings also revealed three significant elements: collegial relationships, teachers assisting other teachers, and school administrators’ support constituted the CS practices in the context of secondary schools in Malaysia. Furthermore, teachers expressed that CS practice had benefited them in reducing the hierarchical form of superiority gap in schools. The findings also revealed that teachers benefited through CS knowledge-sharing practices for professional development, where experienced teachers assist their novice counterparts.